Ocular malignant melanoma – a report of two cases - Reddy, SC; Darnal, HK (Nepalese Journal of Ophthalmology, 2014)
Introduction: Melanoma is a rare malignant tumour in the eye. Objective: To report two cases of malignant melanoma in the eye, one in the conjunctiva and the other in the choroid. Cases: The first case was in a 49-year-old lady who presented with a swelling on the inner side of left upper eyelid. The vision was 6/6. On everting the eyelid, multiple, pigmented, nodular swellings were noted on the tarsal conjunctiva. Excision biopsy confirmed the diagnosis of malignant melanoma of the conjunctiva. A pigmented nodular swelling occurred on the lower bulbar conjunctiva in the same eye one-and-a-half years after the first presentation. There were no secondary nodules in the body. Excision biopsy confirmed malignant melanoma of the conjunctiva. The second case was in a 72-year-old lady who presented with pain and bleeding in the right eye. There was no perception of light. The cornea was hazy and the details behind it could not be seen. There was micro perforation of the cornea with oozing of blood and secondary glaucoma. B-scan ultrasonography of the right eye revealed an intraocular tumour. The histopathology of the enucleated eyeball confirmed the diagnosis of malignant melanoma of the choroid. Conclusion: In the case of conjunctival melanoma, the occurrence of tumour at multiple sites and absence of recurrence at the original site suggests the possibility of de novo origin of the tumour. Secondary glaucoma and bleeding may be the presenting features of melanoma in the choroid. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10783  Nepal J Ophthalmol 2014; 6 (2): 113-118